Factors and common conditions associated with adolescent dietary supplement use: an analysis of the National Health and Nutrition Examination Survey (NHANES) - Gardiner, Paula (BioMed Central, 2008)
BACKGROUND: Little is known about the prevalence of dietary supplement (DS) use in American adolescents. We conducted this study to analyze the prevalence of DS use and factors associated with this use in a national population-based sample. METHODS: We used data from the 1999 – 2002 National Health and Nutrition Examination Surveys (NHANES) for adolescents age 11 to 19. Using weighted logistic regression, we identified demographic and clinical factors associated with the use of any DS, vitamins or minerals, herbs and other DS. RESULTS: Among the 5,306 responses representing approximately 36 million Americans 11–19 years old, 27% reported use of one or more DS in the prior month. The most commonly used DS were: multivitamins (16%) and vitamin C (6%). In the multivariable analysis, African American [adjusted odds ratio 0.40 (0.31–0.50) 95% CI] and Mexican American [0.55 (0.44–0.69)] adolescents were less likely to use DS compared with non-Hispanic whites. DS use was more common in those who used prescription medications [1.37 (1.10–1.72)] and among those who had a diagnosis of chronic headaches [1.25 (1.04–1.50)]. DS use was less common among those reporting fair or poor health status [0.59 (0.40–0.88)]. CONCLUSION: Twenty seven percent of American adolescents use DS. DS use is higher among teens that use prescription medications; physicians and pharmacists should be aware of this, ask patients, and check for potential interactions.